STUDI PERILAKU GAJAH SUMATERA, Elephas maximus sumatranus UNTUK MENDUKUNG KEGIATAN EKOWISATA DI PUSAT KONSERVASI GAJAH TAMAN NASIONAL WAY KAMBAS - Annisa Salsabila; Gunardi Djoko Winarno; Arief Darmawan (Fakultas Biologi | Universitas Jenderal Soedirman, 2017)
Studies of Sumatran elephant behavior that include the typical behavior of each elephant individual is significant to support ecotourism activities. Information on the elephant behavior obtained by scientific observation can be presented to tourists to provide exciting insights and knowledge during their visit to the Way Kambas Elephant Conservation Center (PKG). This study aimed to determine elephant behavior based on gender, age, the origin of capture, the training time, and also to examine the elephant behavior in supporting ecotourism activities in PKG Way Kambas. The results indicated that the behavior of Sumatran elephants could be determined by sex, age, the origin of capture, and the training period. The male elephant has a more aggressive response than female elephants. The mahout efficiently instructed the adult elephants than the baby, toddlers, and youngsters elephants. The elephant's behavior born in PKG compared to those from capture in the wild were different. Those born in PKG were easier to tame than elephants from outside PKG. Duration of training was also influential to elephants behavior, the longer they were trained, the tamer the elephants. The training was prepared to elephants so that the elephants can be safely presented and familiar to tourist to raise fund for PKG primarily to support the elephant caring and handling.